Border rules: an abolitionist refusal - Chowdhury, Kanishka (Politics of citizenship and migration, 2023)
This book examines both border policies and oppositional narratives of “the border,” 2011-2021, demonstrating that the term designates not merely a line of territorial control but also a set of social relations shaped by persistent, racially differentiated colonial structures and, more recently, by neoliberal modes of accumulation. These relations are shown to determine access to wealth and/or resources and to enable the management of labor, the extraction of surplus, and the accumulation of capital. Discussion in the book is informed by the history of these policies and by the critical literature on borders. Various cultural texts focusing on two border zones--the US-Mexico and the EU-Southern Mediterranean--are analyzed: specifically, two novels, two films, and two murals examined in conjunction with a music video. A path to a borderless future is suggested: an abolitionist refusal of border rules with an insistence on the necessity of abolition